The Economic and Societal Cost of Alzheimer's Disease in Australia 2021-2041 - Brown, Laurie; Li, Jinjing; La, Hai Anh (University of Canberra, 2022)
Alzheimer’s disease (AD) is the most common cause of dementia, with the prevalence increasing rapidly with age. It involves the progressive loss of neurons that affects a person’s behaviour, memory and cognitive processes. As cognitive impairment progresses, a person’s ability to maintain their activities of daily living declines and their need for care increases with the growing loss of independence and autonomy. Though the symptomatic burden of dementia typically occurs late in life, it is preceded by a long preclinical phase, characterized by the pernicious accumulation of neuropathology in the brain (Lupton et al., 2020). The project aims to estimate: 1. the societal cost of dementia due to Alzheimer’s disease (AD) in Australia’s population aged 50 and above years under usual care; and 2. the economic impact on both direct and indirect costs of an effective hypothetical disease-modifying therapy (DMT) as an early intervention in persons with mild cognitive impairment (MCI) due to AD or mild dementia due to AD to prevent or delay the progression to more severe dementia health states.
Keywords: Government, law and policy